Opportunities to diagnose chronic obstructive pulmonary disease in routine care in the UK: a retrospective study of a clinical cohort. - Jones, Rupert C M; Price, David; Ryan, Dermot; Sims, Erika J; von Ziegenweidt, Julie; Mascarenhas, Laurence; Burden, Anne; Halpin, David M G; Winter, Robert; Hill, Sue; Kearney, Matt; Holton, Kevin; et al. (Lancet Respir Med, 2014)
BACKGROUND: Patterns of health-care use and comorbidities present in patients in the period before diagnosis of chronic obstructive pulmonary disease (COPD) are unknown. We investigated these factors to inform future case-finding strategies. METHODS: We did a retrospective analysis of a clinical cohort in the UK with data from Jan 1, 1990 to Dec 31, 2009 (General Practice Research Database and Optimum Patient Care Research Database). We assessed patients aged 40 years or older who had an electronically coded diagnosis of COPD in their primary care records and had a minimum of 3 years of continuous practice data for COPD (2 years before diagnosis up to a maximum of 20 years, and 1 year after diagnosis) and at least two prescriptions for COPD since diagnosis. We identified missed opportunites to diagnose COPD from routinely collected patient data by reviewing patterns of health-care use and comorbidities present before diagnosis. We assessed patterns of health-care use in terms of lower respiratory consultations (infective and non-infective), lower respiratory consultations with a course of antibiotics or oral steroids, and chest radiography. If these events did not lead to a diagnosis of COPD, they were deemed to be missed opportunities. This study is registered with ClinicalTrials.gov, number NCT01655667. FINDINGS: We assessed data for 38,859 patients. Opportunities for diagnosis were missed in 32,900 (85%) of 38,859 patients in the 5 years immediately preceding diagnosis of COPD; in 12,856 (58%) of 22,286 in the 6-10 years before diagnosis, in 3943 (42%) of 9351 in the 11-15 years before diagnosis; and in 95 (8%) of 1167 in the 16-20 years before diagnosis. Between 1990 and 2009, we noted decreases in the age at diagnosis (0·05 years of age per year, 95% CI 0·03-0·07) and yearly frequency of lower respiratory prescribing consultations (rate ratio 0·982 opportunities per year, 95% CI 0·979-0·985). Prevalence of all comorbidities present at COPD diagnosis increased except for asthma and bronchiectasis, which decreased between 1990 and 2007, from 281 (33·4%) of 842 patients to 451 of 1465 (30·8%) for asthma, and from 53 of 842 (6·3%) to 53 of 1465 (3·6%) for bronchiectasis. In the 2 years before diagnosis, of 6897 patients who had had a chest radiography, only 2296 (33%) also had spirometry. INTERPRETATION: Opportunities to diagnose COPD at an earlier stage are being missed, and could be improved by case-finding in patients with lower respiratory tract symptoms and concordant long-term comorbidities. FUNDING: UK Department of Health, Research in Real Life.